639 Current developments in bruxism identification (Balneo and PRM Research Journal, 2024)
Background and Objectives: Bruxism is a parafunctional activity that can have several causes. Patients with bruxism need an interdisciplinary approach to treatment planning and individualized treatment options. The present study evaluates dentists' knowledge of the bruxism condition and their need for further education. Diagnosis and treatment methods used by practicians from different specialties are emphasized. Materials and Methods: A prospective cross-sectional, observational, and analytical cohort study was conducted. It employed a questionnaire based on information on etiology, diagnosis, and treatment methods and included data from 80 dental practitioners from Cluj County.Results: Most dentists (81.3%) recognized awake and sleep bruxism as separate entities. Most participants identified psychological status as the primary etiological factor (80%), followed by occlusal interferences (13.8%) and other factors (genetics). Anamnesis and clinical examination were performed for bruxism diagnosis (90%). Occlusal balance (%) and occlusal splints (%) were the most encountered treatment methods. Only 27.5% of the practitioners referred patients to other specialists. Physiotherapy and psychotherapy were the primary interdisciplinary approaches. Cognitive behavioral therapy was employed by 43.8%, whereas pharmaceutical therapy by 20% of the practitioners.Conclusions. There is a need for standardized training among dentists due to a lack of information on this topic. When combined with an interdisciplinary approach, complementary diagnostic methods such as polysomnography and BruxApp can yield accurate diagnosis.Keywords: bruxism, occlusion, stress, polysomnography